PENERAPAN ALGORITMA C4.5 UNTUK MEMPREDIKSI PENJUALAN SAYUR PADA PT BUMI BHAKTI BARELANG - Panjaitan, Tulus Bobi Saen Evansen; Harman, Rika (LPPM Universitas Putera Batam, 2022)
Sales can be said to be the center of the business in the field of marketing, in order to get more profit to continue the business. A good company certainly has long-term goals so that it can experience positive developments in the future. With the rapid development of businesses around the world, not a few businesses are built to get more profits with various forms of sales activities. One of the efforts to maintain business stability is to generate sales predictions. The problem faced by the business world today is that there is often an imbalance between supply and demand for goods. The number of buyers and the variety of tastes in the products they have make it difficult for PT Bhakti Bumi Barelang to predict the best-selling items so that they can predict when these items will run out. To overcome this, a vegetable sales prediction system with the highest consumer demand is needed. This prediction will be very helpful for helping vegetable stock supplies such as PT Bhakti Bumi Barelang which plans vegetable stock supplies and informs companies about the products that are most purchased by consumers.